Fear, Security, and Identity: Behavioral and Perceptual Transformations under Missile Warfare Threats in the US–Israel–Iran Conflict - Srichareun, Mayuree (Thai Social Science Journal, 2026)
This article aims to analyze the role of “fear” and “risk” in shaping behavioral, perceptual, and identity transformations in society under the context of missile warfare between the United States, Israel, and Iran in 2026. The findings reveal that missile warfare has transformed threats from discrete events into a condition of “permanent insecurity,” leading to the production of “social risk” that significantly influences everyday life. Fear does not merely reflect objective risk but is shaped and amplified through media and security discourses, causing individuals to overestimate threats and adjust their behavior accordingly. Such behavioral changes include avoiding risky areas, restricting daily activities, and accepting state-imposed security measures. In terms of perception, the world is increasingly viewed as a dangerous space, while the state is perceived as a protector, resulting in increased trust in state authority under conditions of fear. Simultaneously, fear contributes to the formation of social identity through the construction of “us versus the enemy” and the rise of emotional nationalism, which fosters both social cohesion and polarization.This article argues that risk in contemporary society is not merely an objective condition but a “socially constructed reality” produced and amplified through social processes. In this context, fear becomes a central mechanism that systematically shapes behavior, perception, and identity in modern societies.